Substructure hybrid test examining the seismic response of point-supported glass façades attached to large-span spatial steel structures. (1st September 2022) - Han, Qinghua; Zhao, Yifeng; Lu, Yan; Wang, Shuyu
Highlights: A hybrid test is used to conduct experiment of large-span spatial structures & glass façade coupling system. The glass façade can reduce the acceleration response of mid-span upper chord node of main structure. The DIC method shows the deformation and failure mode of the glass panels. Seismic performance evaluation indexes of point-supported glass facade are determined. Abstract: Point-supported glass façade (PSGF) is one of the most widely used types of non-structural components. Its earthquake damage may not only cause economic loss, but also interruption of building use and even casualties. This paper aims at investigating the seismic response of the large-span spatial structure and PSGF coupling system through the substructure hybrid test. The substructure pseudo-dynamic (PSD) test method is used, that is, the loading rate of the test is slow as that of the quasi-static tests. The finding is that when the glass panel begins to fail, the cracks occur and instantly spread to the whole glass panel along the diagonal direction due to the stress concentration at a bolt hole of double-layer laminated glass, accompanied by looseness of several point-fixed fitting screws. The drift angle of one glass panel is about 50.0%–81.9% of that of glass façade δ in the critical and failure state, indicating that the supporting system can reduce the in-plane deformation of the glass panel. And the glass façade can reduce the acceleration responses of the mid-span upper chord nodes of the large-span spatial structure by 4.74%–13.98%. Finally, the seismic performance evaluation indexes of PSGF are determined based on the drift angle δ and percentage of damaged glass panels for the slight, moderate, and extensive limit states. It will provide an example and reference for the seismic performance evaluation of the PSGF.